Morphological and nutritional description of Yaretzi: a variety of dahlia for cut or potted flower - Martínez-Damián, María Teresa; López-Santiz, Juleni Antonia; Hernández-Epigmenio, Francisca; Sosa-Montes, Eliseo; Cruz-Alvarez, Oscar (Revista Mexicana de Ciencias Agrícolas, 2025)
The genus Dahlia (Asteraceae: Coreopsideae), made up of 42 species characterized by their wide diversity in size, shape, and color of their inflorescences, is highly appreciated for ornamental use and nutritional contribution. The aim of this contribution is to disseminate the morphological and nutritional description of Yaretzi, a variety of dahlia suitable for cut or potted flower. The plant of this variety has a stem diameter of 13.6 mm, 11.29 nodes, 5.78 branches, 90.16 days to flowering, 14.75 flowers, 350.86 g of root weight, 6.97 roots, peduncle diameter of 3.4 mm, and capitula (diameter= 112.36 mm, 138.22 ligules and 170 g of weight). Among the main physicochemical characteristics of ligulate flowers are 5.83 °Brix, 7.81% malic acid, 5.01 mg 100 g-1 vitamin C and 0.08 mg 100 g-1 chlorophyll. Likewise, 1.46 mg kg-1 of total anthocyanins, 0.05 mg Eβ-carotene g-1 (total carotenoids), total phenols (31.52 mg GAE g-1), antioxidant capacity (60.63 and 177.42 μmol TE g-1, FRAP, ABTS, respectively), color components (lower and upper part of the ligula) L*= 67.07-73.29, C*= 55.46-53.44, °h= 24.19-23.31. Among the minerals, the high concentration of Fe2+ and Zn2+ stands out, both nutrients are essential for human health. On the other hand, tuberous roots stood out for having around 24% inulin, a carbohydrate with a promising role as a prebiotic. These results contribute to the diversification of the dahlia, an endemic and microendemic phytogenetic resource of Mexico.